2016
DOI: 10.1186/s13033-016-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis and help-seeking behavior in rural KwaZulu Natal: unearthing local insights

Abstract: BackgroundGrowing interest in strategies regarding early intervention for psychosis has led to a parallel interest in understanding help-seeking behavior, especially in low- and middle-income countries (LMICs). Nevertheless, few LMIC studies have examined individuals with psychosis in non-urban, non-hospital settings. Using the perspective of formal and informal community service providers, we aimed to uncover descriptions of people with psychosis in a rural South African community and illuminate the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
1
22
1
Order By: Relevance
“…Despite these problematic issues, there has been a paucity of research looking at rural mental health care in South Africa. Studies [22,23] have confirmed that pathways to mental health care in rural South Africa are complex. These pathways can include formal western medicine as well as informal traditional medicine, with over half of the cases reporting no contact with formal health care services.…”
Section: Rural Mental Health In South Africamentioning
confidence: 98%
“…Despite these problematic issues, there has been a paucity of research looking at rural mental health care in South Africa. Studies [22,23] have confirmed that pathways to mental health care in rural South Africa are complex. These pathways can include formal western medicine as well as informal traditional medicine, with over half of the cases reporting no contact with formal health care services.…”
Section: Rural Mental Health In South Africamentioning
confidence: 98%
“…Meetings were structured to explore respective notions and understandings of a variety of psychological and behavioral phenomena, with an emphasis on psychotic symptoms using case vignettes. In addition a focus group discussion (with 8 THPs) as well as 10 individual semi-structured interviews with THPs were held to elicit knowledge, attitudes and practices associated with mental illness (again emphasizing psychosis) and its traditional treatment in that community [21]. While it is beyond the scope of this paper to describe the actual worldview of THPs and their understanding of psychotic phenomena, it is relevant here to report that a degree of common ground was discovered during this process.…”
Section: Engagement With Thps To Develop Mutual Understanding Of Tradmentioning
confidence: 99%
“…The regional Traditional Health council provided a list of all "bona fide" THPs, indicating that there are other, less trustworthy practitioners as well, collaboration with whom was deemed undesirable. Better identification of people with psychotic disorder in this rural part of South Africa also is likely to require collaboration with other local key informants with a good knowledge of their community, such as religious leaders, faith healers and police (see Labys et al [21] for a report on this aspect). Previous experiences in our and other regions show that these sources are open for collaboration with formal health care [30].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Others may lack choices, social networks, and face stigma. Labys et al (2016) described help-seeking behavior in rural KwaZulu-Natal and informal networks and informal care providers addressing psychosis, finding that two-thirds of the 32 interviewees were never seen by a formal provider. Their social network supported them with only 1 in 8 accessing a psychiatric hospital, which was actually correlated with functional and social deterioration.…”
Section: Rural and Remote Psychiatrymentioning
confidence: 99%